Zur Ermittlung eines marktgerechten Erbbauzinses. Ein Praktikermodell. - Löhr, Dirk (Springer Gabler, 2017)
In Deutschland findet die Gestaltung von Erbbaurechtsverträgen sehr oft unter politischen Gesichtspunkten, aber wenig am Markt orientiert statt. Die Akzeptanz des Erbbaurechts leidet hierunter. Eine wichtige Rolle spielt dabei die Festlegung des Erbbauzinses, der angesichts des niedrigen Zinsniveaus oft als unangemessen empfunden wird. Andererseits stellt sich die Ableitung "marktgerechter" Erbbauzinsen im Vergleichswege schwierig dar. Im Beitrag wird daher ein praxisbezogener, auf der Kapitalmarkttheorie basierender Ansatz für die Festlegung marktgerechter Erbbauzinsen dargestellt. Wichtig ist dabei die Verschiebung der Rendite/Risiko-Position, die sich aufgrund der Bestellung von Erbbaurechten gegenüber Volleigentum ergibt. Sowohl der Erbbauverpflichtete wie auch der Erbbauberechtigte dürfen sich diesbezüglich nicht schlechter als bei Volleigentum stellen. Diese Anforderung wird durch die Sharpe Ratio konkretisiert. Damit sich der Erbbauberechtigte nicht gegenüber Volleigentum verschlechtert, bedarf es einer "Subventionierung" seiner Rendite. Es wird gezeigt, dass dies durch den Erbbauberechtigten ohne Einbußen in seiner Rendite/Risiko-Position gegenüber Volleigentum geschehen kann. Auf Grundlage dieser Überlegungen werden Mindestrenditeforderungen für den Erbbauberechtigten und Höchstsätze für den Erbbauverpflichteten kalkuliert, die sich auf die Bodenwerte beziehen.

Ground lease contracts in Germany are often primarily designed according to political stipulations instead of market-orientation. This undermines the acceptance of ground leases. An important aspect in this regard is the setting of the annual lease payment, which is often considered as being inappropriate on the background of the low interest level at present. This is why methods have to be identified in order to align the lease payments closer with the market. However, due to the dominance of political motives on the German market of ground leases, the derivation of a market conform ground lease by comparison is mostly inappropriate. This paper therefore presents a practice-oriented approach for assessing the ground lease rates, which is based on the capital market theory. Market-orientation means that, on the one hand, the owner of the land doesn t exploit a strong position in the local real estate market, and, on the other hand, neither the lessor nor the lessee is put into a worse position, compared with real estate in full property. Moreover, the risk/return positions of both the lessee and the lessor have to be balanced. These requirements are put into concrete terms by using the Sharpe-ratio, which should be the same in ground leases and full property investments. Within ground leases the risk/return profile is a different one, compared to full property real estate. This is because by far most of the operational risks are shifted onto the lessee. Therefore, in order to avoid a worsening of the lessee, she needs a higher risk premium and higher returns, compared to full property real estate. On the other hand, the lessor s position is quite safe. Because most of the operational risks are shifted away from the lessor, a ground lease is almost as safe as investments into long-term governmental bonds. Thus the lessor may reduce her risk premium and her return requirements, compared with full property real estate. She may discount her cash flows from the ground lease to a comparatively lower rate. Doing so, the value of the cash flows is comparatively higher, compared to the current returns on the land share within full property real estate. The lessor may use this difference in value in order to subsidize the lessee s profitability, without disadvantages in comparison to full property. This subsidy might either be paid in the form of a single payment to the lessee or by reducing the lessee s current leasehold fees. However, each way implies a different risk/return position for the lessee, with different requirements for the return rates (lessee) and the amount of subsidies (lessor). Based on these ideas, minimum return requirements for the lessees and maximum return requirements for the lessors can be calculated in an easy way, also by practitioners. However, this calculation only makes sense if the amortization of debts is not a preferable investment, in case the debt interest rate is higher than the ground lease rate. Moreover, also the assessment of the risks may turn out to be a problem, particularly in markets with low sales volumes. Finally, the proposed concept is not in line with the current valuation standards for ground leases at least in Germany, since these standards don t reflect the shift in the risk/ return position, which is caused by ground lease arrangements.
Keywords: Bodenwert; Grundstückswert; Rendite; Erbbaurecht; Wertermittlung; Vertragsgestaltung; Erbbauzins